THE TEACHER'S USE OF GESTURES, PROXEMIC SPACE, AND IMAGES IN A MULTIMODAL CLASSROOM - Kamelia, Fitria (2017)
Historically, communication has always involved different modes. A teaching must contain multimodality in nature. However, many teachers rarely pay their thoughtful attention to the language other than verbal language as a means of communication. Also, they are not well-informed about how various modes can creatively produce meaning, and encourage classroom interaction. This research intends to investigate teacher's gesture, use of space, and use of images as the nonverbal modes she has been using. In addition, how these modes are functioned and how they are intersemiotically related with verbal mode are also observed. A model teacher who was teaching in a grade-A boarding school was videotapped and analyzed for three teaching sessions to obtain the data. The finding reveals that among 3 modes (gestures, proxemic space, and images), gestures were the most frequent one used by the teacher. Gestures functioned as controller, resource, prompter, and tutor. Proxemic space functioned in sponsoring, teaching, encouraging, counselling, and befriending. Lastly, images functioned only as an illustrative visual. Furthermore, gestures, space, and images found to have some intersemiotic relationships with verbal mode namely synonymy, meronymy, antonymy, and collocation. These results show that the function of gesture, and space is significantly related with some pedagogical theories like teacher's role theory, and mentoring theory. On the other hand, images seem to have less contribution. The images just act as an illustration which has a passive function in a text. The images do not require the students to respond in a written or spoken form, they are functioned only to give context, and increase motivation. A more significant function of images namely stimulus-response which usually used for specific learning outcomes whether in a spoken or written form do not seem to be put into practice.----- Secara historis, komunikasi selalu melibatkan mode yang berbeda. Sebuah pengajaran harus mengandung multimodalitas. Namun, banyak guru yang jarang memperhatikan dengan sungguh-sungguh keberadaan bahasa selain bahasa verbal sebagai alat komunikasi. Selain itu, mereka juga tidak mengetahui dengan baik bagaimana berbagai mode dapat menghasilkan makna secara kreatif, dan mendorong interaksi dalam kelas. Penelitian ini bertujuan untuk mengetahui apa dan bagaimana seorang guru menggunakan gestur, ruang gerak, dan gambar sebagai mode nonverbal yang telah digunakan. Selain itu, bagaimana mode-mode ini difungsikan dan bagaimana mereka terkait secara semiotis dengan mode verbal juga diamati. Seorang guru teladan yang mengajar di sebuah sekolah swasta yang terakreditasi A direkam dan dianalisis selama tiga sesi pengajarannya guna memperoleh data yang diperlukan. Data yang didapat mengungkapkan bahwa di antara 3 mode (gestur, ruang gerak, dan gambar), gestur menjadi mode yang paling sering digunakan oleh guru. Gestur ini berfungsi sebagai controller, resource, prompter, dan tutor. Ruang gerak guru berfungsi sebagai sponsoring, teaching, encouraging, counselling, dan befriending. Terakhir, gambar hanya berfungsi sebagai ilustrasi visual. Gestur, ruang gerak, dan gambar ditemukan memiliki beberapa hubungan intersemiotik dengan mode verbal yaitu hubungan synonymy, meronymy, antonymy, dan collocation. Hasil ini menunjukkan bahwa fungsi gestur, dan ruang gerak secara signifikan terkait dengan beberapa teori pedagogis seperti teori peran guru, dan teori pendampingan. Di sisi lain, gambar nampaknya kurang memberi kontribusi. Guru hanya menggunakan gambar sebagai ilustrasi yang memiliki fungsi pasif dalam teks. Gambar-gambar yang digunakan tidak mengharuskan siswa untuk memberi respon secara tertulis atau lisan, mereka berfungsi hanya untuk memberi konteks, dan meningkatkan motivasi. Fungsi gambar yang lebih signifikan yaitu stimulus-response yang biasanya digunakan untuk hasil pembelajaran tertentu baik dalam bentuk lisan maupun tulisan tidak dipraktikkan dalam proses pengajaran di konteks ini.